Assistance in the administration system of the Pelangi Waste Bank, Siak Regency - Yandra, Alexsander; Husna, Khuriyatul; Wardi, Jeni (Community Empowerment)
Pelangi Waste Bank is a foster from the Siak Regency Government under the coordination of the Environmental Service (DLH). The activities of the waste bank are quite good, but they still need assistance in marketing by making brochures and bookkeeping administration in the form of savings books. This activity is supported by PT Chevron's CSR funds, which encourage modern institutional governance that is in line with current needs. With a participatory discussion approach, investigation and assistance, the process of preparing brochures and passbooks can run smoothly and according to needs. Even administratively, it has an impact on strengthening the organization, namely the waste bank institution.